ABSURDITIES IN PEDAGOGICAL TEXTS - Alevtina S. Robotova (Высшее образование в России, 2016)
The article is devoted to the language of pedagogical science. As a basic material, the author considers the published dissertation summaries on pedagogy. To attract the attention of the scientific community to this issue, the author has used the word “absurdities”. It conveys the researcher’s negligent attitude to scientific word, so that sometimes text loses its sense. This leads to misunderstanding and creates conceptual barriers, reduces the scientific value of research work.